The Importance of Propionibacterium acnes Place in Microbiology World - KAPTANOĞLU, ASLI FERİDE (GALENOS YAYINCILIK, 2018)
Propionibacterium acnes is most commonly recognized for its acne pathogenesis. However, it is known that P. acnes produces chemotactic substances and activates the compleman system. Recently, it has also been shown to take an important place in the pathogenesis of other diseases and exhibit opportunistic pathogenic properties with increased number of molecular studies. In addition, various studies have been carried out in order to use its effects on the immunity for therapeutic purposes. In this review, the features and pathogenesis of P. acnes have been reviewed in the light of current literature.
Keywords: Propionibacterium acnes; acne vulgaris; pathogenesis; microbiology; opportunistic pathogen; biofilm; RESISTANCE